2022
DOI: 10.1037/pas0001121
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of an observation-based parent–child interaction rating scale for Chinese children aged 0–6 years.

Abstract: We examined the psychometric properties of a parent-child interaction rating scale (IRS) in Chinese children. We recruited 346 dyads of children aged 0-6 years (M age = 2.72 years, SD = 1.52 years) and their caregivers from four cities in China. Parent-child interactions were videotaped in a controlled laboratory and coded by two trained coders. Internal reliability and test-retest reliability were used to measure the reliability of test scores from the IRS in our sample. We performed confirmatory factor analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The ratings of mothers may be subject to social desirability and the mood of the reporter (Gardner, 2000). To reduce such biases, future studies should assess parent‐child relationships using more objective measurements such as observations (Huang et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The ratings of mothers may be subject to social desirability and the mood of the reporter (Gardner, 2000). To reduce such biases, future studies should assess parent‐child relationships using more objective measurements such as observations (Huang et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In our framework, assertion, self-control, and cooperation, respectively, refer to behaviors that initiate social interactions or express opinions, hold back impulsive emotions/ideas/actions, and coordinate or collaborate with others (Gresham, 2001 ). In the existing researches, another scale, named the Interaction Rating Scale (IRS) and its Chinese version (IRS-C), have also been used to observe parent–child interactions and evaluate children’s social skills in both Japan and China (Anme et al, 2010 ; Huang et al, 2022 ; Sugisawa et al, 2010 ), in which key concepts in subdomains are consistent with the descriptions of assertion, self-control, and cooperation in the SSS. Moreover, previous studies also demonstrated that assertion, self-control, and cooperation are related to each other and have long-term effects on child social development (Dunfield et al, 2011 ; Gülseven et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaires, completed by the parents, contain 118 items to assess specific behavioral and emotional problems. The CBCL was translated into Chinese via a two-stage translation process[ 24 ]. The internal consistency and 1-mo test-retest reliability (all α values and reliabilities > 0.6, except for thought problems) of the Chinese version were satisfactory for Taiwanese patients[ 25 ].…”
Section: Methodsmentioning
confidence: 99%